Mortality from external causes in the state of bahia, 2015-2019 (Research, Society and Development, 2022)
Objective: to describe the epidemiological profile of mortality from external causes in the state of Bahia in the period from 2015 to 2019. Methodology: this is a descriptive study, with a temporal design and a quantitative approach that used secondary data from the Mortality Information System (SIM), from the SUS Department of Informatics (DATASUS), which are made available by the Ministry of Health. Results: the findings showed that among the external causes analyzed, aggression was the reason for the highest mortality rates. When analyzing the profile of victims affected by external causes, most are male individuals aged ¬20 to 29 years, brown, with schooling between 4 to 7 years of schooling and the public road was the main place of occurrence of deaths. Conclusion. it was found that during the study period, Bahia showed a trend towards an increase in deaths from external causes, especially with regard to aggression, a preventable death. We believe that based on the findings presented, it is possible to obtain subsidies for the development of public policies aimed at promoting health for the population, as well as reducing deaths from external causes in Bahia and in the country.